2021
DOI: 10.2807/1560-7917.es.2021.26.38.2001321
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus (HCV) incidence among men who have sex with men (MSM) living with HIV: results from the French Hospital Database on HIV (ANRS CO4-FHDH) cohort study, 2014 to 2017

Abstract: Background Despite the availability of highly effective direct-acting antivirals (DAAs) and the expected treatment as prevention (TasP) effect, transmission of hepatitis C virus (HCV) persists in men who have sex with men (MSM) who engage in high-risk sexual behaviours. Aim We aimed to estimate the incidence of primary HCV infection among MSM living with HIV in France when DAA was readily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…The incidence rates of HIV/HCV co-infection in some Asian and European countries were lower than that reported in this study with a rate of 0.88 per 100 person-years in Singapore, 19 and 0.72 and 0.44 per 100 person-years among MSM in France 20 and Italy 21 . A systematic review conducted between 2000 and 2016 reported an incidence rate of 0.78 per 100 person-years among MSM.…”
Section: Discussioncontrasting
confidence: 85%
“…The incidence rates of HIV/HCV co-infection in some Asian and European countries were lower than that reported in this study with a rate of 0.88 per 100 person-years in Singapore, 19 and 0.72 and 0.44 per 100 person-years among MSM in France 20 and Italy 21 . A systematic review conducted between 2000 and 2016 reported an incidence rate of 0.78 per 100 person-years among MSM.…”
Section: Discussioncontrasting
confidence: 85%
“…Evidence from cohorts of PLHIV in high-income countries have shown decreases in primary HCV incidence in recent years, particularly after DAA introduction. [14][15][16][17][18][19][20] However, in some countries, primary incidence was declining before DAA introduction, or trends in incidence have only been analysed during the DAA era. Therefore, it is unclear whether observed incidence reductions would have occurred even without DAAs.…”
Section: Introductionmentioning
confidence: 99%
“…We limited the observation period to the end of 2020 to limit uncertainly in estimates in the final year of data availability as people were censored at their last HCV RNA test with no extra time added and this may result in artificially inflated incidence rates. 16 Testing history prior to the reinfection observation period was included for two reasons. Firstly, some GBM may have been known to have established chronic HCV, and as such may not have had additional HCV RNA testing in close proximity prior to commencing DAA treatment (Figure S1).…”
Section: Eligibilitymentioning
confidence: 99%